Analysis of Potential Business Service Retribution to Regional Original Revenue in Pacitan Regency 2019-2023 - Maharani, Tania Diva; Saputra, Dany Adi (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2024)
This study aims to analyze the potential revenue from business service retribution in Pacitan Regency by utilizing the actual revenue data of the retributions from 2019 to 2023. This research is a qualitative descriptive study. The primary data was obtained from interviews and the secondary data was collected from the financial reports of Pacitan Regency. To analyze the data, the researcher used a potential analysis of the current conditions from 2019 to 2023 and a trend analysis to project estimated revenues. The researcher used the data in the period before the pandemic and after the pandemic for the next four years. The potential analysis results indicate that there are components of business service retribution that potentially need to be improved. These components are fish auction place retribution, with revenue realization of 99.51% of the set budget, and recreational and sports places retribution, with revenue realization of 83.43% of the set budget. The trend analysis predicts an annual increase in revenue of IDR 2,722,774,900.50 according to predictive analytics after the pandemic. Based on this research, several aspects need to be improved to enhance the revenue from business service retribution, particularly concerning the quality of Human Resources (HR). The improvement and addition of facilities at locations as the objects of business service retribution are also needed.